Can Nonprofit Capacity Be Measured?. (June 2017) - Despard, Mathieu R.
Organizational capacity is the set of structures and functions a nonprofit organization needs to effectively serve the community. Although capacity is defined in the nonprofit literature, no standardized measures exist, making it difficult to accurately assess organizational capacity. Data from a survey of nonprofit human service organizations ( N = 1, 221) that participated in a capacity-building demonstration project are used to assess the fit of two conceptual models of capacity using confirmatory factor analysis. Results indicated that a model that measured capacity with more than 40 performance-related indicators did not fit the data well. However, a model using fewer (19) indicators of organizations' self-assessed capacity-building progress fit the data well and was invariant by tenure. Implications for measuring nonprofit organizational capacity are discussed.